The Juridical Impact of the Misuse of Casual Daily Worker (CDW) Status on the Protection of Workers’ Normative Rights in the Coal Transportation Sector in Jambi - Yudistira, Primus; Budhiartie, Arrie; Dewi, Ratna; Nofanda, Syurpana (Yayasan Baru Haji Samsudin, 2025)
This study analyzes the juridical impact of the misuse of Daily Casual Worker (DCW) status on the protection of workers’ normative rights in the coal transportation sector in Jambi Province. In practice, DCW status is frequently applied to workers who perform permanent and continuous work, resulting in legal uncertainty and weakened protection of workers’ rights. This research employs a normative legal research method by examining labor regulations, legal doctrines, and relevant scholarly literature. The findings indicate that the misuse of DCW status contradicts the principles of protection in labor law and leads to the loss of workers’ normative rights, including minimum wage entitlements, social security coverage, occupational safety, and certainty of employment relations. Weak supervision and law enforcement further exacerbate workers’ vulnerability. Therefore, strengthening regulations and oversight is necessary to ensure fair legal protection for workers in the coal transportation sector.